Experiment of adding molybdenum to AISI 310 to increase tensile strength. Issue 1 (February 2021) - Permana, Diki Ismail; Sumirat, Uum; Darwanto, Yoko
Abstract: Supercritical coal power plants began in 1983 with 24.1 MPa moisture parameters and 538°C / 538°C temperature (superheated and reheated steam). Ultra supercritical technology began in 1993 with 24.1 MPa and 538°C / 593°C. Starting in 2000, an ultra-high temperature supercritical power plant was built at 25MPa and 600°C / 620°C in Tachibana and Isogo Powerplants. From this phenomenon, together coal at the power plant, there is often damage to the turbine blade because the material from the turbine blade is not able to withstand temperatures> 760°C. So the words between these can be analyzed by adding molybdenum on AISI 310 raw material in order to find a new material that is resistant to temperature > 760°C. Stainless steel is a steel that has an important role in the industry. One type of stainless steel is austenitic stainless steel. In general, stainless steels containing Ni, Cr and no other blends. The strength and tenacity of the austenitic stainless steel can be increased by alloying and thermo mechanical treatment (TMT). In the integration process, a structure can be carried out which can be improved by the mechanical properties of the material. To find out the austenitic stainless steel needs to be developed to increase resistance to the corrosive environment, and also its mechanical properties. This development can be done by combining AISI 310 with Molybdenum